Systematic literature review and analysis for Arabic text steganography method practically - Roslan, Nuur Alifah; Udzir, Nur Izura; Mahmod, Ramlan; Gutub, Adnan (Elsevier, 2022)
Despite the rapidly growing studies on Arabic text steganography (ATS) noted recently; systematic, in-depth, and critical reviews are in scarcity due to high overlap or low segregation level among the existing review articles linked to this research area. As such, the objective of this paper is to present an extensive systematic literature review (SLR) on the techniques and algorithms used to analyse ATS. Data were retrieved from three primary databases, namely Science direct Journal, IEEE Explore Digital Library, and Scopus Journal. As a result, 214 publications were identified since the past 5 years regarding methods of analysing ATS. A comprehensive SLR was executed to detect a range of unique characteristics from the algorithms, which led to the discovery of a new structure of ATS categories. Essentially, a hybrid method for ATS was identified with other sub-disciplines, especially cryptography, which leads to a new branch in enhancing security for ATS. Other relevant findings included key performance and evaluation criteria used to measure the performance of the algorithms (i.e., capacity, invisibility, robustness, & security). 87 % of the reviewed articles are the capacity measurement performance. Therefore, it disclosed a huge potential for the other two criteria (i.e. invisibility, robustness and security) to set a benchmark for future research endeavour.